2007
DOI: 10.1002/syn.20399
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist‐induced increase in 5‐HT1A‐receptor expression in adult rat hippocampus and cortex

Abstract: Many receptor antagonists function as reverse agonists on the signaling transduction pathway, but little is known about the action of these drugs on the regulation of receptor expression. Serotonin 1A (5-HT1A) receptor expression in 5-HT and serum-free fetal hippocampal cultures is increased in the presence of a specific 5-HT1A-receptor antagonist N-(2-(4-(2-methoxyphenyl)-1-piperazinyl)ethyl)-N-(2-pyridinyl) cyclohexane carboxamide (WAY 100635). To study the plasticity of postsynaptic 5-HT1A receptors in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…1996), and thus the lack of 5‐HT in the Pet‐1 knockout mice may also result in up‐regulation of these post‐synaptic 5‐HT1A receptors. In agreement with this, acute treatment with 5‐HT1A antagonist WAY100,635 was also shown to up‐regulate 5‐HT1A receptor number in cortex and hippocampus (Abbas et al. 2007).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…1996), and thus the lack of 5‐HT in the Pet‐1 knockout mice may also result in up‐regulation of these post‐synaptic 5‐HT1A receptors. In agreement with this, acute treatment with 5‐HT1A antagonist WAY100,635 was also shown to up‐regulate 5‐HT1A receptor number in cortex and hippocampus (Abbas et al. 2007).…”
Section: Discussionsupporting
confidence: 60%
“…Lesion of 5-HT projections to the hippocampus using the 5-HT neurotoxin, 5,7-dihydroxytryptamine, results in increased levels of 5-HT1A protein in the hippocampus (Patel et al 1996), and thus the lack of 5-HT in the Pet-1 knockout mice may also result in up-regulation of these post-synaptic 5-HT1A receptors. In agreement with this, acute treatment with 5-HT1A antagonist WAY100,635 was also shown to upregulate 5-HT1A receptor number in cortex and hippocampus (Abbas et al 2007). The reduction in 5-HT1A RNA levels in the cortex agrees with pharmacological studies demonstrating that reduced 5-HT signalling delays expression of cortical 5-HT type-1 receptors (Whitaker-Azmitia et al 1996;Lauder et al 2000).…”
Section: Regulation Of Tph2 and 5-ht1a Receptor Expression By Pet-1 Isupporting
confidence: 64%
“…However, the effect of the G/G genotype on postsynaptic 5-HT1A receptors is less clear. The G/G genotype in depressed subjects was associated with no change or increased 5-HT1A receptors in some regions such as the hippocampus (21,22,50), which could reflect a compensatory up-regulation due to lower serotonergic neurotransmission in these subjects (52) or a decrease in forebrain Deaf-1 levels, leading to reduced transcription of the 5-HT1A heteroreceptors (53). Several studies report reduced 5-HT1A RNA or binding in the prefrontal cortex of subjects with major depression (24,(53)(54)(55)(56), consistent with reduced transcription of the 5-HT1A receptor.…”
Section: Altered 5-ht1a Receptor Expression In Deaf-1 Knock-outmentioning
confidence: 93%
“…Immunohistochemical and in situ hybridization studies have revealed the presence of 5-HT 1A receptor protein and mRNA in external PFC layers in rat (Abbas et al 2007;Kia et al 1996;Pompeiano et al 1992;Santana et al 2004) and in monkey and human brain (Burnet et al 1995;Cruz et al 2004;DeFelipe et al 2001;Marazziti et al 1994;Mengod et al 1996;Pasqualetti et al 1996).…”
Section: Cellular Localization Of 5-ht 1a In Pfcmentioning
confidence: 99%